Dynamic analysis of the load lifting mechanisms - Vladić, Jovan (Strojniški vestnik, 2008)
This paper deals with the problem of dynamic behaviour of load lifting mechanism (such as elevators). In the case of considerable lifting heights, high velocity devices are applied, with the purpose of shortening cycle duration and increasing the capacity. In such case, the standard procedure of dynamic analysis is not applicable. In the paper, the procedure of establishing the appropriate dynamic model and corresponding equations is proposed. It enables the analysis of the relevant influences, such as variation of the rope free length, slipping of the elastic rope over the drum or pulley and damping due to the rope internal friction.
Keywords: dvigala; škripci; dinamični modeli; stabilnost